Perancangan Konsep Aplikasi Online Marketplace ‘BaBli’ untuk Pengembangan Desa Pintar di Sulawesi Utara - Christopel H. Simanjuntak; Steven N. Rumokoy (Jurnal Teknik Elektro dan Komputer, 2019)
Abstract — Many cities in Indonesia develop smart cities to improve the competitiveness of cities. One city that wants to develop smart city is Manado. However, a city develops if villages develop too. Because of that, development of smart villages is needed to support city to become smart city. According to the Nourth Sulawesi Central Statistics Agency in 2018 [1], there are 1601 villages that receive income from agricultural products. If the agricultural products are exported will increase village income. In addition, distribution chains that are too long make sales difficult. In this research, an online marketplace application concept design was developed under the name 'BaBli'. 'Babli' is taken from the North Sulawesi language which means shopping.In this design, researchers create Block Diagrams, Network Diagrams, Use Case Diagrams, Activity Diagrams, Sequence Diagrams and System interface design. In the Block Diagram there is user interaction with the application via the internet. Network Diagram illustrates the big picture of the network used. In the Use Case Diagram, there are 3 actors who play roles, namely Seller, Operator, User and 19 actions. In the Activity Diagram illustrates the User / Buyer interacting with the System which is divided into 3 diagrams namely Activity Diagram Login, Activity Diagram 1 and Purchase 2. In Sequence Diagram, describes the process of purchasing items where there are 3 Actors namely User / Buyer, Seller and Operator and 1 Object namely System. In the Interface Design, the Search menu is placed in the middle in order to facilitate the User in searching. Item placement is divided into categories so that users can easily navigate in the system.Keywords — BaBli; Design; Online Marketplace;  Smart Village. Abstrak — Banyak kota di Indonesia melakukan pengembangan smart city untuk meningkatkan daya saing kota. Salah satu kota yang mau mengembangkan smart city adalah kota manado. Akan tetapi, kota akan maju jika desanya maju juga. Dikarenakan hal itu, diperlukan pengembangan desa pintar untuk menyokong kota agar menjadi smart city. Menurut Badan Pusat Statistik Sulawesi Utara tahun 2018 [1], ada 1601 desa yang mendapat penghasilan dari hasil pertanian. Jika saja hasil pertanian ini di eksport akan meningkatkan pendapatan desa. Selain itu, rantai distribusi yang terlalu panjang mempersulit penjualan. Dalam penelitian ini, dikembangkan rancangan konsep aplikasi online marketplace dengan nama ‘BaBli’yang diambil dari bahasa sehari-hari Sulawesi Utara yaitu belanja. Pada rancangannya, peneliti membuat Block Diagram, Network Diagram, Use Case Diagram, Activity Diagram, Sequence Diagram dan Perancangan antarmuka sistem. Pada Block Diagram adanya interaksi user dengan aplikasi via internet. Network Diagram mengambarkan gambaran besar akan jaringan yang digunakan. Pada Use Case Diagram, terdapat 3 actor yang berperan yaitu Penjual, Operator, User dan 19 action.  Pada Activity Diagram mengambarkan User/Pembeli berinteraksi dengan Sistem dimana terbagi dalam 3 diagram yaitu Activity Diagram Login, Activity Diagram Pembelian 1 dan Pembelian 2. Pada Sequence Diagram, menjabarkan proses pembelian item dimana ada 3 Actor yaitu User/Pembeli, Penjual dan Operator dan 1 Object yaitu Sistem. Pada Rancangan Antarmuka, menu Pencarian ditaruh di bagian tengah agar supaya memudahkan User dalam pencarian. Penempatan Item dibagi dalam kategori supaya user mudah melakukan navigasi dalam system.Kata kunci : BaBli; Desa Pintar; Perancangan; Online Marketplace.